Requirements for becoming an instructor in the light of current legal regulations in Poland - Wojtanowski, Mateusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The article addresses requirements for becoming an instructor in Poland. The aim of the author is to stress the consequences of the 2011 reform. The paper describes following conditions: a required time of possession of documents stating a particular kind of eligibility to drive depending on a relevant kind of instructor qualifications; possession of valid certificates on the lack of health and psychological contraindications to perform instructor activities; completion of a relevant instructor course (which has to be certified); pass an exam verifying qualifications before an committee appointed by a voivode; lack of specified convictions which follow from a legally valid court sentence; entry in a register of instructors.
Keywords: vehicle; instructor; driving school